Input manipulation, enhancement and processing: Theoretical views and empirical research - Benati, Alessandro (Studies in Second Language Learning and Teaching, 2016)
Researchers in the field of instructed second language acquisition have been examining the issue of how learners interact with input by conducting research measuring particular kinds of instructional interventions (input-oriented and meaning-based). These interventions include such things as input flood, textual enhancement and processing instruction. Although the findings are not completely conclusive on whether these instructional interventions have an impact on acquisition, it is clear that we have witnessed a shift in the field from the original question “Does instruction make a difference?” to the more specific question “Does manipulating input make a difference?” In this article, the key classroom-based research conducted to measure the relative effects of different types of enhancement and manipulation is reviewed. Three main research foci are considered: (a) research measuring the effects of saturating the input with the target form (input flood), (b) research measuring the effects of different types of textual enhancements to draw learners’ attention to the target form, and (c) research measuring input restructuring to improve interpretation and processing of target forms or structures (processing instruction).